2020
DOI: 10.1002/adma.202002723
|View full text |Cite
|
Sign up to set email alerts
|

2D Materials Decorated with Ultrathin and Porous Graphene Oxide for High Stability and Selective Surface Activity

Abstract: 2D black phosphorus (BP) and MXenes have triggered enormous research interest in catalysis, energy storage, and chemical sensing. Unfortunately, the low stability of these materials under practical operating conditions remains a critical bottleneck, particularly as they are prone to oxidization under moisture. In this work, the design and application of stable 2D heterostructures obtained from decorating BP and MXene (Ti3C2Tx) with few‐layer holey graphene oxide (FHGO) membranes are presented. In the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 35 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…For example, the methods of argon cryogenic storage, storage in the organic solvent, , and edge-capping were adopted to mitigate oxidation of Ti 3 C 2 T X flakes. Surface coatings composed of carbon, , conductive polymers, , rGO, , polydopamine, and silicone as the physical barrier were used to stabilize Ti 3 C 2 T X -based assembly. The thermally annealing processing under hydrogen or inert argon gas was used to prepare the dense or sintered Ti 3 C 2 T X films with excellent oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the methods of argon cryogenic storage, storage in the organic solvent, , and edge-capping were adopted to mitigate oxidation of Ti 3 C 2 T X flakes. Surface coatings composed of carbon, , conductive polymers, , rGO, , polydopamine, and silicone as the physical barrier were used to stabilize Ti 3 C 2 T X -based assembly. The thermally annealing processing under hydrogen or inert argon gas was used to prepare the dense or sintered Ti 3 C 2 T X films with excellent oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ] In addition, recent study has revealed that the presence of few‐layer holey graphene oxide (FHGO) in 2D‐based BP/MXene heterostructure membranes can passivate undesired oxidative degradation behaviors of BP or MXene layers and meanwhile achieve the selective molecular diffusion, which will bring some new properties into the 2D‐2D heterostructures and widen their applications. [ 129 ]…”
Section: Synthetic Strategies Of 2d/2d Heterostructuresmentioning
confidence: 99%
“…Since the discovery of graphene in 2004 1 , its intriguing features have piqued the interest of researchers all over the globe in other two-dimensional (2D) nanomaterials for a variety of applications. Porous 2D materials with changeable pore shape and size have attracted a lot of attention because of their potential uses in a variety of applications, including photocatalysis, electrocatalysis, biomaterials science, energy generation, storage 2 4 . Porous materials may interact with a variety of active species both within their porous frameworks and on their surface, but only if these substances fit the pore size of porous materials, which is crucial for gas storage, separation, adsorption, and heterogeneous catalysis 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%